Dietary Omega-3 Polyunsaturated Fatty Acids Suppress NHE-1 Upregulation in a Rabbit Model of Volume- and Pressure-Overload - van Borren, Marcel; Den Ruijter, Hester M.; Baartscheer, Antonius; Ravesloot, Jan Hendrik; Coronel, Ruben; Verkerk, Arie O. (Frontiers in Physiology, 2012)
Background: Increased consumption of omega-3 polyunsaturated fatty acids (3-PUFAs) from fish oil may have cardioprotective effects during ischemia/reperfusion, hypertrophy, and heart failure (HF). The cardiac Na+/H+-exchanger (NHE-1) is a key mediator for these detrimental cardiac conditions. Consequently, chronic NHE-1 inhibition appears to be a promising pharmacological tool for prevention and treatment. Acute application of the fish oil 3-PUFAs eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) inhibit the NHE-1 in isolated cardiomyocytes. We studied the effects of a diet enriched with 3-PUFAs on the NHE-1 activity in healthy rabbits and in a rabbit model of HF induced by volume- and pressure-overload. Methods: Rabbits were allocated to four groups. The first two groups consisted of healthy rabbits, which were fed either a diet containing 1.25% (w/w) fish oil (3-PUFAs), or 1.25% high-oleic sunflower oil (9-MUFAs) as control. The second two groups were also allocated to either a diet containing 3-PUFAs or 9-MUFAs, but underwent volume- and pressure-overload to induce HF. Ventricular myocytes were isolated by enzymatic dissociation and used for intracellular pH (pHi) and patch clamp measurements. NHE-1 activity was measured in HEPES-buffered conditions as recovery rate from acidosis due to ammonium prepulses. Results: In healthy rabbits, NHE-1 activity in 9-MUFAs and 3-PUFAs myocytes was not significantly different. Volume- and pressure-overload in rabbits increased the NHE-1 activity in 9-MUFAs myocytes, but not in 3-PUFAs myocytes, resulting in a significantly lower NHE-1 activity in myocytes of 3-PUFA fed HF rabbits. The susceptibility to induced delayed afterdepolarizations (DADs), a cellular mechanism of arrhythmias, was lower in myocytes of HF animals fed 3- PUFAs compared to myocytes of HF animals fed9-MUFAs. In our rabbit HF model, the degree of hypertrophy was similar in the 3-PUFAs group compared to the 9-MUFAs group. Concl